Вплив параметрів гофрування на основну власну частоту лінійних коливань видовжених циліндричних панелей - Marchuk, M. V.; Марчук М. В.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Національний університет «Львівська політехніка», Львів; Goriachko, T. V.; Горячко Т. В.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Pakosh, V. S.; Пакош В. С.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Lesyk, O. F.; Лесик О. Ф.; Тернопільський національний економічний університет, Тернопіль (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2019)
The relationship between the fundamental natural frequency of linear vibrations of elongated circular cylindrical panels and the amplitude, as well as the frequency of corrugation, is analyzed. The corrugation frequency is set at which the natural frequency of vibrations reaches a minimum. The frequency and amplitude of the corrugation at which the natural frequency reaches the maximum value are revealed. Cite as: M. V. Marchuk, T. V. Goriachko, V. S. Pakosh, O. F. Lesyk, “The influence of parameters of corrugation on the fundamental natural frequency of linear vibrations of elongated cylindrical panels,” Prykl. Probl. Mekh. Mat., Issue  17, 139–146 (2019) (in Ukrainian), https://doi.org/10.15407/apmm2019.17.139-146